Paederus dermatitis: A case series - Sahana Srihari; Ashwini P Kombettu; Kanthraj G Rudrappa; Jayadev Betkerur (Wolters Kluwer Medknow Publications, 2017)
Vorderman (1901) was the first to record blisters caused by beetles in medical literature. Blister beetle dermatitis is a cutaneous condition caused by the toxins released by blister beetles. The vesicant chemical in the body fluids of these insects causes an acute irritant contact dermatitis characterized by erythematovesicular lesions associated with burning sensation on exposed parts of the body. The aim of this study was to investigate the morphological patterns of blister beetle dermatitis. We conducted a 1-year (January-December 2014) prospective study of the clinical presentation of Paederus dermatitis noticed in urban and semiurban areas close to paddy fields in the Cauvery Basin, Mysuru, Karnataka. All patients with Paederus dermatitis attending the outpatient department of Department of Dermatology were recruited in the study with a total of 37 patients. Diagnosis was made on detailed history regarding onset of lesions, symptoms, as well as thorough clinical examination of the lesions. The peak time of presentation was June-September, the monsoon season in this part of India. The average duration of lesions at the time of presentation was 2-5 days. All patients had a history of burning and itchy sensation at night followed by full blown lesions the next morning, with the face, neck, and arms being the most common sites. Patients were predominantly males with the age range of 13-55 years. The most common presentations were linear erythematous plaques and erythematovesicles with a "burnt" appearance and a gray necrotic centre. "Kissing" lesions and periorbital involvement were seen in 5 and 6 patients, respectively. Species identification of the Paederus beetles was not done. Paederus dermatitis occurs in tropical regions. Awareness about the morphological patterns of the condition will prevent misdiagnosis. Simple preventive measures can be undertaken based on the behavioral pattern of this nocturnal beetle.